PENGARUH LITERASI KEUANGAN, GAYA HIDUP, DAN FINANCIAL DISTRESS TERHADAP PERILAKU KEUANGAN MAHASISWA JURUSAN AKUNTANSI POLITEKNIK NEGERI MEDAN PENGARUH LITERASI KEUANGAN, GAYA HIDUP, DAN FINANCIAL DISTRESS TERHADAP PERILAKU KEUANGAN MAHASISWA JURUSAN AKUNTANSI POLITEKNIK NEGERI MEDAN - Lili Sri Ayu Harahap; Selfi Afriani Gultom; Meily Surianti; Anita Putri; Davit Andryan Pakpahan (Jurnal Akuntansi dan Bisnis, 2026)
This study aims to analyze the effect of financial literacy, lifestyle, and financial distress on the financial behavior of accounting students at Politeknik Negeri Medan. This research employed a quantitative approach by distributing questionnaires to 100 students as respondents. Data were analyzed using multiple linear regression with SPSS 27. The results indicate that financial literacy, lifestyle, and financial distress have a positive and significant effect on students’ financial behavior. The adjusted R² value of 0.432 indicates that 43.2% of the variation in financial behavior can be explained by the three independent variables, while the remaining 56.8% is influenced by other factors outside the model. These findings highlight the importance of financial literacy in shaping students’ healthy financial behavior, as well as the need to control lifestyle and manage financial conditions to avoid financial distress.